An analysis of variation in performance of union parishad: a case study of six union parishads of Sirajgong district. - Hikmat, Mirza Tarik (Center for Governance Studies, BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Governance and Development, 2007.